2005
DOI: 10.1038/sj.jhh.1001884
|View full text |Cite
|
Sign up to set email alerts
|

Randomised controlled trial of qigong in the treatment of mild essential hypertension

Abstract: Exercise and relaxation decrease blood pressure. Qigong is a traditional Chinese exercise consisting of breathing and gentle movements. We conducted a randomised controlled trial to study the effect of Guolin qigong on blood pressure. In all, 88 patients with mild essential hypertension were recruited from the community and randomised to Goulin qigong or conventional exercise for 16 weeks. The main outcome measurements were blood pressure, health status (SF-36 scores), Beck Anxiety and Depression Inventory sco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
157
1
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(161 citation statements)
references
References 20 publications
1
157
1
2
Order By: Relevance
“…Although hundreds of different styles are now practiced worldwide, all consist of three basic components: controlled breathing, meditation, and smooth, continuous, purposeful movement. Qigong has been shown to reduce sympathetic activation and enhance cardiovagal tone both acutely and long-term in clinical 10,11 as well as nonclinical populations. 12 A growing body of research suggests that qigong, like other forms of meditation practice, may promote beneficial changes in the central nervous system, including favorable changes in dopaminergic and other neurochemical systems 13,14 as well as increases in blood flow, oxygen delivery, and glucose use in specific regions of the brain associated with mood elevation, memory, and attentional processing, including the hippocampus, prefrontal cortex, and anterior cingulate gyrus.…”
Section: Introductionmentioning
confidence: 99%
“…Although hundreds of different styles are now practiced worldwide, all consist of three basic components: controlled breathing, meditation, and smooth, continuous, purposeful movement. Qigong has been shown to reduce sympathetic activation and enhance cardiovagal tone both acutely and long-term in clinical 10,11 as well as nonclinical populations. 12 A growing body of research suggests that qigong, like other forms of meditation practice, may promote beneficial changes in the central nervous system, including favorable changes in dopaminergic and other neurochemical systems 13,14 as well as increases in blood flow, oxygen delivery, and glucose use in specific regions of the brain associated with mood elevation, memory, and attentional processing, including the hippocampus, prefrontal cortex, and anterior cingulate gyrus.…”
Section: Introductionmentioning
confidence: 99%
“…Initial trials have suggested that qigong is effective in reducing perceived stress 11,12 and blood pressure. 13,14 Given these reports, there is an ongoing need for further studies to extend these findings to evaluate the effectiveness of qigong in specific treatment groups. In addition, since there are over 1000 forms of qigong extant, it is important to determine whether some types of qigong are more effective than others in reducing stress.…”
mentioning
confidence: 99%
“…However, individuals with PPS undergo these typically age-related changes precociously, experiencing such things as a substitution of lean mass for fat and hypersensitivity to cold 26 . Several studies have demonstrated that Chinese exercises (Qìgōng 氣功) have, as one function, a modulation of the autonomic nervous system (sympathetic) [31][32][33][34][35] . Our study suggests that DQ provides an increase in internal temperature through the voluntary contraction of muscles in the pelvic cavity (during expiration) that are associated with diaphragmatic excursion (during inspiration).…”
Section: Discussionmentioning
confidence: 99%